Human Resource Development Strategies Analysis for Competitiveness Enhancement: A Case Study of Jopuro Nature Tourism - Yakin, Aditya Ainul; Rohmatullah, Bintang Farih; Solicha, Dewi Khotimatus; Rozik, Moch. Choirul; Rosyidah, Elok (International Publisher, 2025)
This study aims to analyze human resource development strategies, the role of local culture, and their impact on improving tourism competitiveness in Jopuro Nature Tourism. The method used is a descriptive qualitative method with a case study approach. Data collection was carried out through observation, in-depth interviews with Jopuro nature tourism managers, Pokdarwis, the Kampung Anyar village government, and tourists, as well as documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing models. Then, data validity testing was conducted. The results showed that development strategies can be implemented through regular training, institutional strengthening (AD/ART), and inclusive recruitment based on the principle of